CPR Induced Inappropriate Shocks from a Subcutaneous Implantable Cardioverter Defibrillator during Out-of-Hospital Cardiac Arrest. (2nd January 2020) - Cmorej, Patrik; Smrzova, Eva; Peran, David; Bulikova, Tana
Abstract: We present the case of a 30-year-old man with a subcutaneous implantable cardioverter defibrillator (S-ICD) who suffered sudden out-of-hospital cardiac arrest. During resuscitation, the patient received inappropriate shocks due to oversensing by the S-ICD of chest compression induced artifact. The rhythm on the EMS monitor showed asystole throughout the period of resuscitation. Placement of a magnet over the S-ICD generator failed to inhibit the delivery of S-ICD shocks. Information regarding inappropriate S-ICD shocks may be useful during resuscitation of patients with sudden cardiac arrest.